2021
DOI: 10.3906/sag-2011-139
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive indicator for the severity of COVID-19: thiol

Abstract: Background/aim: Thiol status is a good reflector of the cellular redox and have vital roles in various cellular signaling pathways. The purpose of the study was to investigate thiol status in patients with SARS-CoV-2 infection.Materials and methods: A total of 587 subjects (517 patients/70 healthy controls) were enrolled in the study.The patients were categorized into the groups regarding to the severity of disease (mild, moderate, severe, and critical).Thiol status of all groups were compared. Results:The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 25 publications
(61 reference statements)
2
30
0
2
Order By: Relevance
“…In another remarkable study, Erel et al calculated the optimal cut‐off value of the thiol level as 323 µmol/L between the control group and the patient group, which they had formed by 517 COVID‐19 patients of all severity. 17 It seems highly probable that the higher cut‐off value in our study is since our patients had a diagnosis of COVID‐19 with only mild and moderate clinical course. Interestingly, we calculated that thiol could also be used in differentiating classic and variant COVID‐19 patients, with a very similar cut‐off value.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In another remarkable study, Erel et al calculated the optimal cut‐off value of the thiol level as 323 µmol/L between the control group and the patient group, which they had formed by 517 COVID‐19 patients of all severity. 17 It seems highly probable that the higher cut‐off value in our study is since our patients had a diagnosis of COVID‐19 with only mild and moderate clinical course. Interestingly, we calculated that thiol could also be used in differentiating classic and variant COVID‐19 patients, with a very similar cut‐off value.…”
Section: Discussionmentioning
confidence: 78%
“… 16 Similarly, Erel et al revealed that the thiol level was significantly low in patients with a diagnosis of COVID‐19, the thiol levels were negatively associated with the severity of the disease, and thiol status could be a useful biomarker in predicting the severity of COVID‐19. 17 Since severe COVID‐19 patients were excluded in our study, the design of our study was not suitable for investigating the relationship between COVID‐19 severity and thiol. However, the significantly lower thiol levels in the patient group supported the hypothesis that thiol was reduced because the immune system used it during COVID‐19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to the one found in another study where it was demonstrated that COVID-19 patients' course with low levels of thiols and that their level can even be a marker that reflects the gradual increase in the severity of the infection [62]. This result is very important because different investigations have reported that the treatment with agents capable of elevating the reducing thiol groups such as GSH, allicin, garlic and N-acetylcysteine, can restore the homeostasis of thiols and decrease the degree of viral infection increasing the TAC and decreasing the LPO in COVID-19 patients [63].…”
Section: Discussionmentioning
confidence: 99%
“…Lung inflammation can stimulate transcription factors such as NF-κβ, which regulate the expression of proinflammatory and antioxidant genes. 18 …”
Section: Discussionmentioning
confidence: 99%